KIAA1429 promotes infantile hemangioma regression by facilitating the stemness of hemangioma endothelial cells. Issue 4 (10th January 2023) - Wang, Luying; Zou, Yuqing; Huang, Zhishun; Wang, Wenjing; Li, Jing; Bi, Jianhai; Huo, Ran
Abstract: Infantile hemangiomas are common vascular tumors with a specific natural history. The proliferation and regression mechanism of infantile hemangiomas may be related to the multilineage differentiation ability of hemangioma stem cells, but the specific mechanism is not well elucidated. KIAA1429 is an N 6 ‐methyladenosine methylation‐related protein that can also exert its role in a methylation‐independent manner. This study aims to explore the function of KIAA1429 in infantile hemangiomas. qRT‐PCR, western blotting, and immunostaining were performed to verify the expression of KIAA1429. The endothelial and fibroblast‐like phenotypes of hemangioma endothelial cells were detected after KIAA1429 knockdown and overexpression. The stemness properties of hemangioma endothelial cells and the underlying mechanism of KIAA1429 in hemangiomas were also investigated. Nude mouse models of infantile hemangiomas were conducted to ascertain the effects of KIAA1429 in vivo. The results showed that KIAA1429 was highly expressed in infantile hemangiomas, particularly in involuting hemangiomas. In vitro experiments confirmed that KIAA1429 inhibited the endothelial phenotype, enhanced the differentiation ability, and promoted the fibroblast‐like phenotype of hemangioma endothelial cells by inducing endothelial cell transition to facultative stem cells. However, the effect of KIAA1429 on the potential target was shown to be independent of N 6 ‐methyladenosine methylation modification. Mouse models further revealed that KIAA1429 could inhibit the proliferation and promote the regression of hemangiomas. In conclusion, this study found that KIAA1429 played an important role in the regression of infantile hemangiomas by enhancing the stemness of hemangioma endothelial cells and could be a potential treatment target for infantile hemangiomas. Abstract : This study explored the expression and function of KIAA1429 in infantile hemangiomas in vivo and in vitro. The results demonstrated that KIAA1429 could inhibit the endothelial phenotype of hemangioma endothelial cells and promote the transition of hemangioma endothelial cells to facultative stem cells. The enhanced stemness of hemangioma endothelial cells facilitated their differentiation to fibroblasts and adipocytes, thus promoted the regression of infantile hemangiomas.